Psikologi Manusia dalam Al-Qur’an dan Hadits - Sabarrudin, Sabarrudin; Syarifah, Indri; Ardimen, Ardimen; Samad, Duski (ANWARUL, 2023)
Special creatures, perfect and created in the best way and given reason or advantages over other creatures, namely humans. When humans do not understand themselves, humans will experience many problems. The purpose of this research is to reveal about human psychology in the Qur'an and Hadith. The type of research is literature review by collecting data from Google Scholar, journals and books, the data is analyzed using data analysis techniques in the form of content analysis. The results of the research show that basically human nature is that humans are religious beings (religious monotheism), humans are caliphs on earth and are born with a fitrah (religious nature). At this stage of development, humans are required to win their essence and the dynamics of human personality consist of spirit, lust, mind and heart physically or physically and the second is psychological.